Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - Carpenter, Lucy; Fleming, Z. L.; Read, K. A.; Lee, J. D.; Moller, S. J.; Hopkins, J. R.; Purvis, R. M.; Lewis, A. C.; Müller, K.; Heinold, B.; Herrmann, H.; Fomba, K. Wadinga; et al. (Journal of atmospheric chemistry, 2010)
Observations of the tropical atmosphere are fundamental to the understanding of global changes in air quality, atmospheric oxidation capacity and climate, yet the tropics are under-populated with long-term measurements. The first three years (October 2006-September 2009) of meteorological, trace gas and particulate data from the global WMO/Global Atmospheric Watch (GAW) Cape Verde Atmospheric Observatory Humberto Duarte Fonseca (CVAO; 16° 51′ N, 24° 52′ W) are presented, along with a characterisation of the origin and pathways of air masses arriving at the station using the NAME dispersion model and simulations of dust deposition using the COSMO-MUSCAT dust model. The observations show a strong influence from Saharan dust in winter with a maximum in super-micron aerosol and particulate iron and aluminium. The dust model results match the magnitude and daily variations of dust events, but in the region of the CVAO underestimate the measured aerosol optical thickness (AOT) because of contributions from other aerosol. The NAME model also captured the dust events, giving confidence in its ability to correctly identify air mass origins and pathways in this region. Dissolution experiments on collected dust samples showed a strong correlation between soluble Fe and Al and measured solubilities were lower at high atmospheric dust concentrations. Fine mode aerosol at the CVAO contains a significant fraction of non-sea salt components including dicarboxylic acids, methanesulfonic acid and aliphatic amines, all believed to be of oceanic origin. A marine influence is also apparent in the year-round presence of iodine and bromine monoxide (IO and BrO), with IO suggested to be confined mainly to the surface few hundred metres but BrO well mixed in the boundary layer. Enhanced CO2 and CH4 and depleted oxygen concentrations are markers for air-sea exchange over the nearby northwest African coastal upwelling area. Long-range transport results in generally higher levels of O3 and anthropogenic non-methane hydrocarbons (NMHC) in air originating from North America. Ozone/CO ratios were highest (up to 0.42) in relatively fresh European air masses. In air heavily influenced by Saharan dust the O3/CO ratio was as low as 0.13, possibly indicating O3 uptake to dust. Nitrogen oxides (NOx and NOy) show generally higher concentrations in winter when air mass origins are predominantly from Africa. High photochemical activity at the site is shown by maximum spring/summer concentrations of OH and HO2 of 9 × 106 molecule cm−3 and 6 × 108 molecule cm−3, respectively. After the primary photolysis source, the most important controls on the HOx budget in this region are IO and BrO chemistry, the abundance of HCHO, and uptake of HOx to aerosol.